Implementation of Imam Al-Ghazali's Perspective Character Values in Nahwu Learning at UMALA - Dian Risky Amalia; Miftahul Huda; Sugirma; Ahmad Fadhel Syakir Hidayat; Siti Sulaikho (Department of Arabic Teaching, Faculty Tarbiyah, Universitas Darussalam Gontor, 2024)
Many perpetrators of fraud are found from academics and become the focus of problems that educators are vulnerable to face in the learning process. Causing public attention on the competence of educators who lack in instilling character values in their learning. Internalization of character values in Nahwu learning from Imam Al-Ghazali's perspective is a valid goal in this study, namely in balancing between science and charity. The research method is descriptive and uses a quantitative approach, namely the Likert scale with non-Probability sampling techniques, namely total sampling of third semester students majoring in Arabic Language Education. This research produces four main characters of Imam Al-Ghazali's persp ective, namely wisdom, courage, airiness, and justice that can be internalized in Nahwu learning. The results showed that 96% strongly agreed, agreed and moderately, and 4% disagreed, so it was not only the theory of Nahwu rules that they got but also the character values that they could apply together. Based on the balance between knowledge and charity that has an impact on their social dimension and is the key to gaining happiness in this world and the hereafter.